Barriers to Sustainable Practices towards Low Carbon Emission Projects in Malaysia - M. A. Klufallah, Mustafa; Othman, Idris; Fadhil Nuruddin, Muhd; Faris Khamidi, Mohd (International Journal of Engineering and Technology, 2018)
The Malaysian constructionÂ industryÂ significantlyÂ contributesÂ Â as an empowerment to its developmentÂ visionÂ ofÂ 2020Â byÂ reducing up to 40% of carbon emission. Moreover, the industry accounts as threat to the environment, notÂ onlyÂ inÂ termsÂ of naturalÂ resourcesÂ consumption butÂ alsoÂ in emitting million tons of carbon emission annually. In fact, Malaysia is categorized the 30th inÂ theÂ worldâ€™sÂ rankingÂ inÂ carbonÂ emissionÂ level. Several studies attempt to investigate and review barriers that face construction stakeholders in order to provide integration of sustainability in construction industry. However, the barriers were lacking in terms of addressing carbon emission aspects of sustainable practice and limit the emissions from construction projects in Malaysia. This paper investigates the major barriers of organization in achieving sustainabilityâ€™s best practice. The identified barriers from the perspective of construction stakeholders in Malaysia were categorised based on factor analysis, which are professional and capacity, design and technologies, cost and finance, and, knowledge and culture.Â Â